2020
DOI: 10.1093/aob/mcaa121
|View full text |Cite
|
Sign up to set email alerts
|

Associations between phytohormones and cellulose biosynthesis in land plants

Abstract: Abstract Background Phytohormones are small molecules that regulate virtually every aspect of plant growth and development; from basic cellular processes, such as cell expansion and division, to whole plant environmental responses. While the phytohormone levels and distribution thus tell the plant how to adjust itself, the corresponding growth alterations are actuated by cell wall modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 197 publications
0
18
0
Order By: Relevance
“…According to some authors, the resulting decrease in pH has led to a loosening of the wall structure, either through the rupture and reconstitution of non-cellulosic polysaccharides normally binding cellulose microfibrils, or through the action of a new class of proteins called expansins, which break hydrogen bridges between wall polysaccharides [30]. Indeed, gibberellins promote a transverse arrangement of microtubules, located immediately below the plasma membrane, and control the orientation of those of cellulose and, consequently, the great longitudinal growth or root elongation [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, the resulting decrease in pH has led to a loosening of the wall structure, either through the rupture and reconstitution of non-cellulosic polysaccharides normally binding cellulose microfibrils, or through the action of a new class of proteins called expansins, which break hydrogen bridges between wall polysaccharides [30]. Indeed, gibberellins promote a transverse arrangement of microtubules, located immediately below the plasma membrane, and control the orientation of those of cellulose and, consequently, the great longitudinal growth or root elongation [31].…”
Section: Discussionmentioning
confidence: 99%
“…INA, as structural SA analogue, could stimulate cellulose synthesis. This polysaccharide is precisely regulated by growth factors, and previous studies have suggested the relation between SA and cellulose accumulation [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall synthesis is tightly regulated by phytohormones, particularly ABA. Both ABA synthesis and signaling are involved in secondary cell wall thickening and lignification [ 110 , 111 ]. SnRK2 kinases, namely, SnRK2.2, 2.3, and 2.6, regulate secondary wall biosynthesis by physically interacting with a NAC family transcription factor, namely NAC secondary wall thickening promoting factor 1 (NST1).…”
Section: Regulation Of Plant Response To Salt Stressmentioning
confidence: 99%